Analysis Of Digital Trends In Public Libraries Of Balochistan - Zaman, Farzana (Journal of Quranic and Social Studies, 2022)
The current study investigated the user perception of digital trends and its challenges in public libraries of Balochistan. The main objectives of the study were to examine digital trends resources and to highlight the challenges using digital trends resources in public libraries of Balochistan. The study used survey design due to its suitability in the given circumstances. The population of the study comprised of 17953 permanent members in all the 17 public libraries in Balochistan. Sample of the study was randomly selected from the permanent members/users, of accessible population of public libraries in Balochistan. A sample of 510 permanent members /users (male/female) was selected randomly. Questionnaire was designed after a vast study of related literatures. A questionnaire was administered through mail and self-visits to the users randomly. To analyze the data, SPSS (Statistical Package for the Social Sciences) software was used to get results. Descriptive analysis was used to analyze the data. It was concluded that digital basic trends are the basic parts of any digital library. The data revealed that most of the public libraries are lacking with the facility of digital trends. Users are facing a number of challenges regarding digital trends in the Public libraries in Balochistan. The Government of Balochistan should endeavor to make an effort to upgrade the non-digital Public libraries into digital libraries in order to enable users effectively utilize and benefit from these new library technologies as most of the public libraries are running under the Government of Balochistan, Culture, Tourism & Archive Department. Training and workshops must be organized for the librarians and the supporting staff of the public libraries to update their knowledge according to the digital trends so that they would be able to run digital libraries effectively and assist their users proficiently.